Progression, Management, and Outcome of Aortic Valve Stenosis in Systemic Sclerosis: A Case Series - Andrea Vergara; Antonio Orlando; Eleonora Caiazza; Serena Vettori; Giovanna Cuomo; Paola Argiento; Emanuele Romeo; Rosa Franzese; Berardo Sarubbi; Michele D’Alto (Journal of Cardiovascular Development and Disease)
Background: In systemic sclerosis (SSc), cardiac involvement is frequent, heterogeneous, and related to a poor prognosis. Due to a longer life expectancy, the development of degenerative aortic stenosis (AS) is not uncommon. The aim of this article is to report the characteristics of AS in SSc, analyzing the rate of progression, the management, and the outcome. Methods: This is a case series conducted at the Department of Cardiology of Monaldi Hospital, Naples, Italy. Results: From January 2007 to December 2022, we analyzed 234 patients with SSc. Ten/234 patients (4.3%) showed severe AS and were included in the analysis (age 75.5 years [IQR 58–84], nine females). Nine had limited and one diffuse SSc. Two patients were in NHYA/WHO II and eight in NYHA/WHO III. All had degenerative three-leaflet AS. Two patients showed severe AS at the first evaluation, and eight developed severe AS during the follow-up, with a time progression from moderate to severe AS of 3.2 ± 1.1 years (progression rate −0.190 ± 0.012 cm2/year for aortic valve area, 8.6 ± 6.1 mmHg/year for mean aortic gradient, 16 ± 7 mmHg/year for peak aortic gradient, and 0.5 ± 0.3 m/s/year for aortic peak velocity). Seven out of 10 patients underwent transcatheter aortic valve implantation (TAVI), one underwent surgical aortic valve replacement (SAVR), one was left untreated, and one was on a waiting list for TAVI. No major complications after TAVI or SAVR occurred. At a mean follow-up of 5.9 ± 3.9 years, eight patients are alive and two died. Conclusion: Severe AS is a relevant cardiac complication of SSc and must be considered in the screening and during the follow-up. Its rapid progression rate may tentatively be due to autoimmunity, degenerative burden, and chronic inflammation.